Estado, economia e educação: uma relação conflitiva e um caminho alternativo para superação das desigualdades sociais - Dílson Passos Junior (Revista de Ciências da Educação, 2016)
For decades the Brazilian Public School has been marked by the low level in the binomial teaching/learning. The political power has demonstrated unable to introduce an organic and efficient education system. The constant changes of goals and educational policies of each government prevent the configuration of a school that effectively prepare children and young people for access to public universities. This paper proposes that the capital used to the Public Schools may be injected into the private sector, offering funding of education for the popular classes from the market laws. Promote a healthy competitive-ness between community and private schools in attracting students financed by the State is the way to overcome an education institution model that has shown – with rare exceptions – unable to offer quality education.